Cardiac Function Outcomes Following Mitral Valve Replacement: A Comparative Analysis of Different Surgical Techniques Based on Our Experiences - Sharma, Praman; Yadav, Lokesh; Yadav, Dipak Kumar; Agrawal, Subhadra; Pokhrel, Amritraj (Journal of Nobel Medical College, 2025)
Background: Mitral valve replacement is an essential treatment for mitral valve disease. Preserving both anterior mitral leaflet and posterior mitral leaflet during mitral valve replacement can yield good resultsin terms of left ventricular fraction. The study aims to examine whether retaining both leaflets is more advantageous compared to preserving none or only the posterior leaflet, particularly concerning left ventricular function.Materials and Methods: This retrospective study includes 77cases of mitral valve replacement performed over three years in the Nobel Medical College and Teaching Hospital. Demographics, co-morbidities, preoperative, perioperative and postoperative outcomes in terms of left ventricle ejection fraction were noted in pre-structured questionnaires. The ethical clearance was taken from the Institute Review Committee, Nobel Medical College and Teaching Hospital.Results: The study categorized patients into three groups based on their surgical techniques: Posterior mitral leaflet preservation (group I), both leaflet excision (group II),and both leaflet preservation (group III).The mean age of the patients was 43.56 years, with 62.3% being female and 55.8% having thyroid disorder. Atrial fibrillation being most common arrhythmia involving 52 (66.67%). Marked difference in preoperative and postoperative ejection fraction, group I 48.9 ± 7 to 51.9 ± 5.7 (Z= -3.405, p=0.001), group II 53.9 ± 6 to 39.2 ± 6.6 (Z= -3.405, p=0.001) and group III 47 ± 6.9 to 47.1 ± 9.5; t (16) = 0.26, p=0.798respectively. There was significant clinical improvement in New York HeartAssociation functional class.Conclusion: This study shows that patients with leaflet preservation technique had good results in terms of improvement in New York Heart Association class, left ventricular ejection fraction and reduction in left ventricle dimensions.